The Geography of Borders: The Method - Ancel, Jacques (Geopolítica(s). Revista de estudios sobre espacio y poder, 2016)
This text is a first that the author would develop later. It is illustrated with case studies and original terminology. It begins with a brief conceptual contribution on the difference in approach between the German and French geographical schools, and continues with a reflection on the historical and geographical relativity of the boundary. Subsequently, at its greatest extent, the article provides a taxonomy of states: amorphous states, in three cases, that of the "savage peoples" without boundaries, of black Africa; that of semi-civilized peoples of northwest Africa, and the particular case of European civilized nomads, called ―terranovas‖. Framed states, with borders undergoing processes of emergence or extension, especially the case of Yugoslavia. And, in addition, some references to stable boundaries of Albania and the Netherlands